The global burden of neurological disorders: translating evidence into policy. Issue 3 (March 2020) - Feigin, Valery L; Vos, Theo; Nichols, Emma; Owolabi, Mayowa O; Carroll, William M; Dichgans, Martin; Deuschl, Günther; Parmar, Priya; Brainin, Michael; Murray, Christopher
Summary: Neurological disorders are the leading cause of disability and the second leading cause of death worldwide. In the past 30 years, the absolute numbers of deaths and people with disabilities owing to neurological diseases have risen substantially, particularly in low-income and middle-income countries, and further increases are expected globally as a result of population growth and ageing. This rise in absolute numbers of people affected suggests that advances in prevention and management of major neurological disorders are not sufficiently effective to counter global demographic changes. Urgent measures to reduce this burden are therefore needed. Because resources for health care and research are already overstretched, priorities need to be set to guide policy makers, governments, and funding organisations to develop and implement action plans for prevention, health care, and research to tackle the growing challenge of neurological disorders.